Do ambitious entrepreneurs benefit more from training?. (6th July 2022) - Kotha, Reddi; (Bala) Vissa, Balagopal; Lin, Yimin; Corboz, Anne‐Valérie
Abstract: Research Summary: Does growth training help entrepreneurs scale‐up new ventures? Our field experiment answers this question using data from 181 Singapore‐based, early‐growth entrepreneurs drawn from a broad range of industry sectors. Treatment content focused on three growth‐catalyst tools relevant for formulating and executing innovation‐led growth: business‐model design, leveraging external networks, and building internal teams. Treatment format comprised interactive lecture sessions and workshops on these tools supplemented by personalized coaching in applying the tools to entrepreneurs' specific challenges. We find that ventures led by entrepreneurs that received training experienced sales growth of 72.5% compared to 30.3% for those in the control condition. Furthermore, ventures led by entrepreneurs with more ambitious growth expectations experienced sales growth of about 100% compared to 10% for those in the control condition. Managerial Summary: We study how training in growth‐catalyst tools help entrepreneurs scale‐up new ventures. We focused on three tools relevant for formulating and executing innovation‐led growth: business‐model design, leveraging external networks, and building internal teams. The training format comprised lecture workshops and personalized coaching in applying the tools. Our quantitative findings confirm that entrepreneurs who attended the training increased their venture's sales revenue, and the more ambitious entrepreneurs increased their venture's sales revenue to a much greater degree. Illustrative interviews suggest these tools help entrepreneurs to reimagine their business, successfully access influential resource‐holders such as potential investors or customers, and persuade them by representing their business in a credible and succinct fashion. Our findings inform policymakers designing entrepreneurial training interventions on how participants' ambitions shapes intervention success.